IMPLEMENTASI PROGRAM REHABILITASI DISABILITAS FISIK (studi Di Pusat Rehabilitasi Terpadu Penyandang cacat Provinsi D.I. Yogyakarta) - , Ana Sukaton, S.I.P; , Dr. Agus Heruanto Hadna, M.Si, ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Tectonic earthquake that hit Yogyakarta Province at May 27 th , 2006 has brought to increasing number of disabled people in Yogyakarta. This condition driven the Yogyakarta Government to create a new social policy, one of them is by building Pusat Rehabilitasi Terpadu Penyandang Cacat at Pundong. This policyâs aim is to develop the welfare of persons with disabilities by integrated rehabilitation between medical and social. This research is aimed to discover the implementation of persons with disabilities integrated rehabilitation at the Pusat Rehabilitasi Terpadu Penyandang Cacat and what factors are causing it. The utilized research method is descriptive â qualitative and by using quantitative data that processed from secondary data. The used technic in collecting data are indepth interview, observation, and documentation study. The utilized theory in this research is to explore data, including social problems observation, disabled people, social policy, and social service, as well as the factors that cause the program implementation The research resulted that the integrated rehabilitation in Pusat Rehabilitasi Terpadu Penyandang Cacat that includes the preparation and formation of Rehabilitation Center task force that has a main task to escort and coordinate the rehabilitation activities before Rehabilitation Center Institutional was formed, and rehabilitation service steps that includes the recruitment, selection, acceptance and placement in program, sheltering, social rehabilitation, and medical rehabilitation are still low in achievement. From many service activities, it found out that the recruitment that was done by the third party encountered data distortion. The selection also done without clear instrument so that when itâs in acceptance process, the accepted client isnât appropriate with the required that has been agreed. The sheltering aspect from facility side is capable enough. While medical rehabilitation was done only limited to general healthcare service. The social rehabilitation is not yet optimal as well, since the guidance activities that were done without considering the client real need, even the advanced channelization and guidance were not done The identified factors that affect the program implementation are there are no clear program standard, that caused confusion of implementation in the field. The next factor is low communication between stakeholders, either internal or external. While the third factor is the resource, there is lack of resource